Erythritol catabolism by Brucella abortus. - Sperry, J F (1975)
Cell extracts of Brucella abortus (British 19) catabolized erythritol through a series of phosphorylated intermediates to dihydroxyacetonephosphate and CO-2. Cell extracts required adenosine 5'-triphosphate (ATP), nicotinamide adenine dinucleotide (NAD), Mg2+, inorganic orthophosphate, and reduced glutathione for activity. The first reaction in the pathway was the phosphorylation of mesoerythritol with an ATP-dependent kinase which formed d-erythritol 1-phosphate (d-erythro-tetritol 1-phosphate). d-Erythritol 1-phosphate was oxidized by an NAD-dependent dehydrogenase to d-erythrulose 1-phosphate (d-glycero-2-tetrulose 1-phosphate). B. abortus (US-19) was found to lack the succeeding enzyme in the pathway and was used to prepare substrate amounts of d-erythrulose 1-phosphate. d-Erythritol 1-phosphate dehydrogenase (d-erythro-tetritol 1-phosphage: NAD 2-oxidoreductase) is probably membrane bound. d-Erythrulose 1-phosphate was oxidized by an NAD-dependent dehydrogenase to 3-keto-l-erythrose 4-phosphate (l-glycero-3-tetrosulose 4-phosphate) which was further oxidized at C-1 by a membrane-bound dehydrogenase coupled to the electron transport system. Either oxygen or nitrate had to be present as a terminal electron acceptor for the oxidation of 3-keto-l-erythrose 4-phosphate to 3-keto-l-erythronate 4-phosphate (l-glycero-3-tetrulosonic acid 4-phosphate). The beta-keto acid was decarboxylated by a soluble decarboxylase to dihydroxyacetonephosphate and CO-2. Dihydroxyacetonephosphate was converted to pyruvic acid by the final enzymes of glycolysis. The apparent dependence on the electron transport system of erythritol catabolism appears to be unique in Brucella and may play an important role in coupling metabolism to active transport and generation of ATP.